Biophysical potential of organic cropping practices as a sustainable alternative in Switzerland. (May 2020) - Lee, Juhwan; Necpálová, Magdalena; Six, Johan
Abstract: Little is known about the potential of adopting organic farming at regional scales for mitigating agricultural greenhouse gas (GHG) emissions. We simulated the effect of organic matter addition (manure and compost) on all cropland soils in Switzerland, with reduced tillage and winter cover cropping in combination. The DayCent model was run for the period 1991–2013 by accounting for factors such as soils, land use, and climate to evaluate alternative practices. Converting conventional cropping with only chemical fertilizers to organic cropping led to a regional mitigation in soil GHG emissions by 0.34–1.10 Mg CO2 -eq ha −1  yr −1 . Soil organic C (SOC) stocks increased by 104–259 kg C ha −1  yr −1, accounting for 86–100% of the GHG mitigation. Adopting organic practices with reduced tillage or cover cropping increased SOC stocks up to 433 kg C ha −1  yr −1 . Our results suggest that the alternative practices could reverse C decline in conventional soils, predicted to be −241 kg C ha −1  yr −1 . Organic practices combined with reduced tillage or cover cropping had varying effects on N2 O emissions, ranging from a mean decrease of −0.60 kg N ha −1  yr −1 to an increase of 0.29 kg N ha −1  yr −1 . Model results suggest the need to deliver mitigation that is more permanent with the careful combination of alternative practices. Also, risks such as increased N2 O emission, especially when using organic amendments with high N decomposition potential, and yield penalty must be managed. Highlights: We simulated the regional effect of organic cropping on greenhouse gas (GHG) emissions from croplands in Switzerland. Organic cropping led to a regional mitigation in soil GHG emissions by 0.34–1.10 Mg CO2 -eq ha -1  yr -1 . 86–100% of the GHG mitigation was due to the increase in soil organic carbon. There is the need to deliver mitigation that is more permanent with the careful combination of alternative practices.